Cloning, expression and serodiagnostic potential of HSP70 of Taenia multiceps in sheep - Kilinc, Seyma Gunyakti; Simsek, Sami; Celik, Figen; Kesik, Harun Kaya (Elsevier, 2021)
The aim of this study was to determine the efficacy of the recombinant protein expressed by the T. multiceps HSP70 gene in the immunodiagnosis of sheep coenurosis. Specific primers were designed to amplify the gene encoding HSP70 from the whole genome sequence of T. multiceps, mRNA was isolated from C. cerebralis cysts obtained from an infected sheep's brain, and then, cDNA was isolated. The gene region related to the designed primers was amplified by PCR, and the obtained product was cloned and expressed. The specificity of the recombinant protein purified afterwards was demonstrated by Western Blot using known positive and negative sheep sera. Additionally, the efficiency of the recombinant protein in ELISA was determined with sera collected from 1207 sheep. Finally, the sensitivity and specificity values of the recombinant TmHSP70 antigen in the Western Blot were 100 %, while the sensitivity and specificity rates of the ELISA were 66.6 % and 52.6 %, respectively. At the same time, 567 (46.97 %) of the 1207 analyzed serum samples were found to be positive by ELISA. In conclusion, the Western Blot technique had a higher quality than ELISA in detecting the TmHSP70 antigen for the serodiagnosis of sheep coenurosis.
Keywords: Taenia multiceps; HSP70; Cloning; Sheep